Reduction in Delayed Gastric Emptying Following Non-Pylorus Preserving Pancreaticoduodenectomy by Addition of a Braun Enteroenterostomy - Nikfarjam, Mehrdad; Houli, Nezor; Tufail, Farrukh; Weinberg, Laurence; Muralidharan, Vijayaragavan; Christophi, Christopher (JOP. Journal of the Pancreas, 2012)
Context Delayed gastric emptying is a major cause of morbidity following pancreaticoduodenectomy. Objective The impact of a Braun enteroenterostomy on delayed gastric emptying, used in reconstruction following classic pancreaticoduodenectomy, was assessed. Patients Forty-four consecutive patients undergoing non-pylorus preserving pancreaticoduodenectomy from 2009 to 2011 by a single surgeon were included in this study. Interventions The first 20 patients had a standard antecolic gastroenterostomy and the subsequent 24 had the addition of a Braun enteroenterostomy. Results Patient characteristics, the extent of surgery, surgical findings and tumor characteristics were similar between the two groups. The delayed gastric emptying rate in the Braun enteroenterostomy (1/24, 4.2%) was significantly lower (P=0.008) than the standard reconstruction group (7/20, 35.0%). In the standard group, 6 of 7 cases (85.7%) of delayed gastric emptying were class C in nature. After exclusion of 8 total pancreatectomy patients, the pancreatic fistula rate in the Braun enteroenterostomy group (4/19, 21.1%) was similar (0.706) to the standard reconstruction group (5/17, 29.4%) as was the median length of hospital stay (10 days vs. 15 days; P=0.291). Braun enteroenterostomy technique was the only significant independent factor associated with reduced delayed gastric emptying with an odds ratio of 0.08 (95% confidence interval: 0.01-0.73; P=0.025). Conclusion The use of Braun enteroenterostomy following non-pylorus preserving pancreaticoduodenectomy appears to result in a significant reduction in delayed gastric emptying. Image: Reconstruction with the addition of Braun enteroenterostomy.